2013
DOI: 10.1097/mjt.0b013e318254259b
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Comparative, Multicentric Clinical Trial to Assess the Efficacy and Safety of Zileuton Extended-Release Tablets With Montelukast Sodium Tablets in Patients Suffering From Chronic Persistent Asthma

Abstract: Leukotriene (LT) modifiers are anti-inflammatory drugs that are useful as an add-on therapy with first-line asthma-controller medications. This group includes LT synthesis inhibitors (eg, Zileuton) and receptor antagonists (eg, Montelukast), whose direct comparative clinical data are not available. This study was conducted to assess the comparative efficacy and safety of orally administered Zileuton extended-release (ER) with Montelukast sodium in patients suffering from chronic persistent asthma. Patients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The potential of blocking this pathway in the treatment of conditions of chronic inflammation is highlighted by the use of zileuton to improve pulmonary function in children and adults with mild-to-severe asthma [38,39]. Cysteinyl leukotriene receptor 1 and 2 (i.e., CysLT-R1 and CysLT-R2) antagonists such as montelukast and zafirlukast [40,41] are also available in some countries, however zileuton is the only Food and Drug Administration (FDA) approved anti-leukotriene inhibitor.…”
Section: 5-lipoxygenase Pathway In Cancermentioning
confidence: 99%
“…The potential of blocking this pathway in the treatment of conditions of chronic inflammation is highlighted by the use of zileuton to improve pulmonary function in children and adults with mild-to-severe asthma [38,39]. Cysteinyl leukotriene receptor 1 and 2 (i.e., CysLT-R1 and CysLT-R2) antagonists such as montelukast and zafirlukast [40,41] are also available in some countries, however zileuton is the only Food and Drug Administration (FDA) approved anti-leukotriene inhibitor.…”
Section: 5-lipoxygenase Pathway In Cancermentioning
confidence: 99%
“…Clinical trials evaluating zafirlukast, montelukast, and pranlukast have shown a decrease of eosinophil count in blood and airways of asthmatic patients (60, 61). However, other studies (62, 63) suggest that the development of dual CysLT1/2R antagonists might bring additional advantages to the asthma treatment over the current used CysLT1R blockers. In fact, patients with chronic persistent asthma presented superior improvement in lung function when treated with a cysLT synthesis inhibitor compared to a CysLT1R antagonist (62).…”
Section: Targeting Cysltrs In the Treatment Of Eosinophilic Disordersmentioning
confidence: 99%
“…However, other studies (62, 63) suggest that the development of dual CysLT1/2R antagonists might bring additional advantages to the asthma treatment over the current used CysLT1R blockers. In fact, patients with chronic persistent asthma presented superior improvement in lung function when treated with a cysLT synthesis inhibitor compared to a CysLT1R antagonist (62). However, recently, a clinical study with a dual CysLT1/2R blocker, the compound ONO-6950, in non-smoking subjects with mild allergic asthma, showed no additional benefits of this therapeutic strategy to the treatment of asthma (64).…”
Section: Targeting Cysltrs In the Treatment Of Eosinophilic Disordersmentioning
confidence: 99%
“…For instance, treatment with the BLT1 antagonists BIIL284, CP105696, and U-75302 reduces atherosclerosis (Ketelhuth et al, 2015), insulin resistance (Li et al, 2015), and chronic obstructive pulmonary disease (COPD) (Dong et al, 2016), respectively. Finally, a 5-LOX inhibitor, zileuton, which inhibits the synthesis of both LTB 4 and Cys-LT, has been approved for the treatment of chronic asthma (Kubavat et al, 2013) and is being investigated as a treatment for colon polyps (Gounaris et al, 2015), sickle-cell disease (Quarmyne et al, 2013), and stroke (Costa Silva et al, 2015).…”
Section: Biosynthesis During Inflammatory Responses Intracellularmentioning
confidence: 99%